The transculturation of Judge Dee stories : a cross-cultural perspective - Wei, Yan (Professor of literature) (Abingdon, Oxon ; New York : Routledge, 2023)
"This book views the Dutch Sinologist, Robert van Gulik's Judge Dee mysteries as a hybrid East-West form of detective fiction and uses the concept of transculturation to discuss their hybrid nature with respect to their sources, production, and influence. The Judge Dee Mysteries authored by Robert van Gulik (1910-1967) were the first detective stories to be set in ancient China. These hybrid narrative combine Chinese historical figures, traditional Chinese crime literature and Chinese history and material culture with ratiocinative methods and psychoanalytic themes familiar from Western detective fiction. This new subject and detective image won a global readership, and the book discusses the innovations that van Gulik's Judge Dee mysteries brought to both Chinese gong'an literature and Western detective fiction. Furthermore, it introduces contemporary writers from different countries who specialize in writing detective fiction or gong'an novels set in ancient China. The book will meet the interest of fans of Judge Dee stories throughout the world, and will also appeal to both students and researchers of comparative literature, Chinese literature, and crime novels studies"--
Keywords: Gulik, Robert Hans van, -- 1910-1967 -- Criticism and interpretation; Detective and mystery stories -- History and criticism; LITERARY CRITICISM / Asian / Chinese; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh